Business Ethics and the Decision to Adopt Golden Parachute Contracts: Empirical Evidence of Concern for All Stakeholders - Evans, Jocelyn D. (Journal of business ethics, 2009)
Golden parachutes are often viewed as a form of excessive compensation because they provide senior management with substantial payouts following an acquisition while other stakeholders are subjected to layoffs, disrupted business relationships and other negative externalities. Using a sample of S&P 500 firms, an economic and ethical justification for this type of contract is given. Golden parachutes ensure effective corporate governance that, in turn, preserve the firm's value for all stakeholders. Boards of directors enter into parachute agreements to protect recently hired CEOs' human capital during periods of financial uncertainty and, thus, potential takeover activity. From an ethics viewpoint, golden parachutes are valuable to all stakeholders because they encourage merger or acquisition in lieu of bankruptcy.